2012
DOI: 10.1177/0363546512448320
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Dorsal Cutaneous Branch of the Sural Nerve

Abstract: The standard lateral approach to the base of the fifth metatarsal carries a higher risk for surgical injury to the LDCN. A "high and inside" approach that remains superior to the superior border of the PBT is anatomically safe and may decrease the chance of intraoperative nerve injury and irritation postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Subsequently, a surgical “safe zone” for incision and dissection during the proximal approach to the 5MT was proposed with the intent to minimize iatrogenic injury to the LDCN and AB. We found the mean vertical distance from the LDCN to the most proximal aspect of the 5MT was 0.8 cm, which is similar to that observed by Fansa et al 10 (0.9 cm). This finding confirms the close proximity of the LDCN when making the lateral approach to the proximal fifth metatarsal (LA-5MT).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Subsequently, a surgical “safe zone” for incision and dissection during the proximal approach to the 5MT was proposed with the intent to minimize iatrogenic injury to the LDCN and AB. We found the mean vertical distance from the LDCN to the most proximal aspect of the 5MT was 0.8 cm, which is similar to that observed by Fansa et al 10 (0.9 cm). This finding confirms the close proximity of the LDCN when making the lateral approach to the proximal fifth metatarsal (LA-5MT).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, several instances were observed in which the LDCN resided superior to the PBT at its insertion onto the 5MT (n = 12; 10%). This observation, combined with our upper and lower distribution frequencies for the vertical distance from the LDCN and AB to the 5MT, respectively, led us to propose a modified “safe zone” building off of the work of Fansa et al 10 Our proposed incision is made more than 1 to 2 mm superior to the PBT and resides between 1.2 and 1.6 cm superior to the most proximal aspect of the 5MT, shown in Figure 5. This incision would remain superior to the LDCN and inferior to the AB in >95% of our analyzed MRI studies.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Careful dissection through the subcutaneous tissues to the base of the fifth metatarsal will protect the peroneus brevis and the sural nerve. Surgeons are less likely to injure the lateral dorsal cutaneous branch of the sural nerve when using a percutaneous approach to fifth metatarsal fractures compared to the standard lateral approach based on cadaveric studies [15]. Utilizing a tissue sleeve for all steps described, a guide wire is placed into the dorsal and medial aspect base of the fifth metatarsal near the metatarsal-cuboid articulation.…”
Section: Treatmentmentioning
confidence: 99%